(untitled) (Law, State and Telecommunications Review, 2019)
Purpose ”“ This article seeks to examine the possibility and limits of judicial control of regulatory agencies decision-making power in Brazil based on the ideas of communicative action and integrity proposed by Jürgen Habermas. Methodology/approach/design ”“ There will be made an analysis of the decisions of the Superior Court of Justice regarding the charge of long-distance-like calls within the same municipality or between conurbated municipalities. Findings ”“ Superior Court of Justice, in most of its cases, privileges the technical criteria adopted by the regulatory agency, understanding that the judicial review would be an improper invasion of a “technical” area. However, there are decisions of the same Court that kept the judicial review carried out by the Courts of Appeal, in flagrant contradiction. The lack of a more consistent reasoning and, above all, of consistency among the decisions reveal the lack of attention on the part of the Brazilian Superior Court of the criteria of integrity advocated by Jürgen Habermas.